Case Report: Coexisting cardiac cavernous hemangioma and sarcoidosis in a single lesion: a first reported case confirmed by surgical resection - Xiao, Chuan-Yong; Han, Wen-Ya; Wang, Han-Sheng; Qian, Xin; Yuan, Ling-Ling; Wang, Mei-Fang; Liu, Yu-Quan (Frontiers in Cardiovascular Medicine, 2025)
Cardiac hemangioma (CH) is a rare benign cardiac tumor whose clinical manifestations—including arrhythmias, heart failure, and pericardial effusion—vary by anatomical location. Sarcoidosis is a multisystem disorder of unknown etiology characterized by non-caseating granulomas, commonly involving the lungs, eyes, and skin, with cardiac involvement being relatively uncommon. To date, no cases of concurrent cardiac hemangioma and cardiac sarcoidosis have been reported worldwide. We herein describe a patient with established sarcoidosis who, during follow-up, exhibited progressive enlargement of a cardiac mass. Surgical resection confirmed the co-existence of cardiac hemangioma and cardiac sarcoidosis within the same anatomical region. Based on these findings, we propose a pathophysiological mechanism wherein cardiac sarcoidosis causes microvascular injury, leading to structural alterations that may promote the development of cardiac hemangioma. The following report details the diagnostic and therapeutic course of this patient.